Anterior chamber bacterial contamination in cataract surgery - Valdez-García, Jorge E (BioMed Central, 2014)
BACKGROUND: The incidence of postoperative endophthalmitis has reduced during last several years to <0.01%; however, its associated complications continue to be devastating. Several sources of infection, including contamination by air, solutions, surgical instruments, intraocular lens, and wound leakage have been identified. The objective of this study was to evaluate the surgical technique, antibiotics, and asepsis that are used to reduce the risk of infection during cataract surgery. METHODS: This was a transversal prospective study, in which 64 cataract surgeries were evaluated from 32 patients, with 1 month recovery time; and cultures from preoperative and postoperative aspirates were analyzed. Two groups were established based on whether preoperative antibiotics were given or not. The analysis employed descriptive statistics. RESULTS: Of the 32 patients whose aspirates were obtained, three (9.37%) and 10 (31.25%) yielded positive cultures preoperative and postoperatively respectively. Staphylococcus species was the most common contaminating bacteria. The isolation of Staphylococcus species may indicate its potential as exogenous contaminant at time of wound closure. The cultures obtained from patients using preoperative antibiotics were positive for S. aureus in 10% (n = 2) of cases, and positive in 8.33% (n = 1) of cases not using antibiotics. The mean transoperative time with positive growth was 67 ± 17.8 minutes, and with negative growth was 76.3 ± 25.2 minutes. Two surgical techniques were evaluated: phacoemulsification and extracapsular extraction. The extracapsular technique showed a contamination rate of 33.33% (n = 8) compared to phacoemulsification with a rate of 25% (n = 2) (RR = 1.33). CONCLUSIONS: Common contaminating microorganisms included the Staphylococcus species, which was isolated from the eyelids and ocular annexes at the time of wound closure. The isolation of microorganisms postoperatively could have been influenced by the surgical technique used, the surgical time, and the use of antibiotics.